Uttag av energisortiment vid gallring av contorta - Gardmo, Fredrik (2007)
A recommendation for stand treatment of lodgepole pine (Pinus contorta) is, in a scientific point of view, lacking when it comes to harvesting for biomass energy. Within the next decades it is expected that 280 000 hectares of lodgepole pine will have reached thinning age on the domains of Svenska Cellulosa Aktiebolaget (SCA). Due to this the interest has grown rapidly for studying the possibilities of harvesting biofuel assortments already in the first thinning.